Scaling Diversification Options In Rice-Based Systems: Insights And Lessons Learned From 2022 To 2025 - Suh, Neville Ndohnwi; Doumbia, Salif; Dossou Yovo, Elliott Ronald (2025)
Diversification in rice-based systems has emerged as a critical strategy to enhance climate resilience, improve farm profitability, and strengthen food and nutrition security in Mali. As climate change intensifies rainfall variability, seasonal unpredictability, pest pressure, and soil degradation, rice monoculture alone no longer provides a stable production system. Between 2022 and 2025, the AICCRA Mali program supported the scaling of diversified farming practices, including rice–legume systems, rice–fish integration, vegetable rotations, agroforestry options, and by-product valorization, all aimed at helping farmers reduce climate risks, restore or maintain soil health, and increase income. A key diversification intervention promoted by the AICCRA project is the provision of solar-powered irrigation pumps, enabling farmers to engage in off-season vegetable production through the Pay-as-you-go (PAYG) scheme. Under this initiative, over 4,483 farmers (60% of whom are women) have benefited from the solar-powered irrigation scheme, supporting dry-season cultivation of important crops. Moreover, over 3658 farmers are engaged in rice-fish farming, of whom about 3% are women.